2019
DOI: 10.1007/s40415-019-00534-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing drought tolerance in field-grown sunflower hybrids by chlorophyll fluorescence kinetics

Abstract: Drought is one of the most damaging abiotic stress factors commonly experienced by plants, resulting in a significant loss of crop yield worldwide. The aim of the study was to assess drought tolerance of sunflower (Helianthus annuus) hybrids and find out potentially underlying photobiological traits. Experiment was conducted in the agricultural field of Eastern Mediterranean Agricultural Research Institute in Adana. To evaluate the drought tolerance of twenty-six sunflower hybrids polyphasic chlorophyll fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 59 publications
(81 reference statements)
2
9
0
Order By: Relevance
“…The performance index is more sensitive to abiotic stresses than the QY of PSII (F v /F m ) (Çiçek et al, 2019;Zivcak et al, 2009). The rate of cates that drought-tolerant cultivar reduces the effective antenna size and absorbed energy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The performance index is more sensitive to abiotic stresses than the QY of PSII (F v /F m ) (Çiçek et al, 2019;Zivcak et al, 2009). The rate of cates that drought-tolerant cultivar reduces the effective antenna size and absorbed energy.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, substantial increase in the relative variable fluorescence (ΔV OI ) and smaller amplitude of I step only in the drought‐sensitive cv. NM‐54 suggested that drought stress caused a disturbance in the intersystem electron transport that resulted in limited electron transport to the last electron acceptor of PSI as observed in sunflower inbred lines under drought stress (Çiçek et al, 2019). The drought stress increased (20%) ΔIP in the drought‐tolerant cultivar NM‐13‐1 Tol , while it decreased in drought‐sensitive cv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aims of this study were (1) to elucidate the adaptation mechanisms of two traditional apple cultivars to drought-stressed conditions in comparison with commercial cultivar; (2) to obtain information about the genetic potential of drought stress tolerance of these traditional cultivars for the future production and breeding of new apple cultivars. Measuring chlorophyll a fluorescence has been widely used as a non-destructive method to analyze the structure and function of the photosynthetic apparatus, particularly PS II, under different abiotic stresses, including drought stress [26][27][28]. In this study we investigated the drought tolerance of selected apple cultivars by OJIP (chlorophyll a fluorescence analysis).…”
Section: Introductionmentioning
confidence: 99%
“…Maximum Quantum Efficiency of PSII of Dark Adapted Plants (FV/FM) is the ratio of variable fluorescence to maximum fluorescence, which is the measurement of maximum quantum yield of PSII, and the alterations of this parameter are correlated with degradation of membrane integrity. Performance Index on Absorption Basis (PIABS) is an aggregated performance index parameter that hosts three independent parameters that cumulatively quantify total functionality of the electron flux through PSII and indicates the vitality of the plant [26]. Absorption Flux per Reaction Centre (ABS/RC) specifies effective antenna size by proportioning absorbed photons to active reaction centers, and an increase of ABS/RC indicates a C 0 is the state in which all seeds are grown under control conditions for 15 days at 25 • C. Until this state, the seeds are allowed to be germinated in controlled conditions and seedlings have 4-5 leaves.…”
Section: Cold Stress Datasetmentioning
confidence: 99%